Pengaruh Peran Guru Agama Islam Dan Keteladanan Orang Tua Terhadap Peningkatan Kedisiplinan Ibadah Anak Di SDN 1 Japan Ponorogo - Muhammad Sholihin; Moh Asvin Abdur Rohman; Samsudin Samsudin (BASICA, 2025)
This study was written with the aim of examining the influence of the role of religious teachers and parental role models on improving children's religious discipline at SDN 1 Japan Ponorogo. 1. Is there an influence of the role of religious teachers on improving students' religious discipline at SDN 1 Japan Ponorogo? 2. Is there an influence of parental role models on improving students' religious discipline at SDN 1 Japan Ponorogo? 3. How is the correlation between the role of religious teachers and the role model of parents of students at SDN 1 Japan Ponorogo? 4. Is there an influence of the role of religious teachers and parental role models on improving students' religious discipline at SDN 1 Japan Ponorogo? This research approach uses a quantitative descriptive method. with data obtained through questionnaires and documentation. Then using data analysis techniques by means of normality test, linearity test, homogeneity test, T test, F test, person product moment correlation and multiple linear regression. The results of the study stated that the role of religious teachers influenced the improvement of students' religious discipline at SDN 1 Japan Ponorogo with a correlation coefficient (f count)) of 4,150 with a probability of 0.000 which is below 0.05. parental role models influence the improvement of students' religious discipline at SDN 1 Japan Ponorogo Based on the interpretation of the correlation coefficient t count, the t count was obtained at 0.434 with a probability of 0.000 which is below 0.05. Correlation between the role of religious teachers influences the role model of parents of SDN 1 Japan Ponorogo. The level of correlation or strength of the relationship, it is concluded that the correlation of X1 to X2 is 0.388 which means the correlation is strong. the role of religious teachers and the role model of parents influence the increase in the discipline of worship of students of SDN 1 Japan Ponorogo with the regression coefficient of the increase in student discipline of worship is 0.166